Effect of Gundelia tournefortii extract in some physiological and biochemical parameters changes induced by Pseudomonas aeruginosa (Journal of the College of Basic Education, 2022)
The present study was carried to evaluate antibacterial activity of Alcoholic and Aqueous water extracts (cold and hot) of Gundelia tournefortii against bacteria Pseudomonas aeruginosa. Antibiotic Sensitivity was done for isolated bacteria used in this study. Results showed variation in antibacterial activity of different extracts against bacteria by paper disc technique in agar and measuring the diameter of inhibition zone at concentration (500,400,300,200,100, 50, 25, 12.5, 6.25 μg / ml). The alcohol extract showed the highest inhibitory effect against the studied bacteria. The hot and cold water extract showed no effect on bacterial growth by measuring the diameter of the (Inhbiition Zone). The minimum inhibitory concentration (MIC) of the alcohol extract was determined to be 300 mg / ml and minimum bacterial concentration ( MBC) for the studied bacteria was 500 mg / ml for the alcohol extract. The efficacy of alcoholic extracts of Gundelia tournefortii was tested in vivo for treatment of Pseudomonas aeruginosa isolates. The tests showed positive results of short-term healing of the infected area compared with the antibiotic used. The results of the biochemical tests of the animals treated with the extract were proven to be 200 and 500 mg / Kg for 10 days by not having a poisonous effect.